Finite elements their design and performance - MacNeal, Richard H. (Mechanical engineering (Marcel Dekker, Inc.), 1994)
In this work, MacNeal examines why finite elements sometimes fail and how element designers have corrected their failures. It includes quantitative analyses of failure modes and illustrations of possible side effects found in proposed remedies, providing a practical understanding of finite element performance. The book is designed to enable users and practitioners to identify and circumvent the major flaws of finite elements, such as locking, patch-test failure, spurious models, rigid-body failure, induced anisotropy and shape sensitivity.